Determination of Soft Soil Permeability Parameters Using Plaxis 2D Based on Settlement Plate Monitoring Data - Bagas Hendi Pratama; Yudhi Lastiasih; Herman Wahyudi (Interdisciplinary Social Studies, 2026)
Road infrastructure development on soft soils often faces geotechnical challenges in the form of large and time-consuming settlement. Discrepancies often occur between analytical settlement predictions and actual conditions in the field. This study aims to determine valid soil permeability parameters (k) through the back calculation method using Plaxis 2D numerical modeling calibrated with settlement plate monitoring data. The research employs a quantitative analytical approach combining field monitoring, observational methods, and finite element numerical simulation to establish representative soil parameters for consolidation analysis. The research methodology includes interpretation of soil investigation data (Borlog and CPTu), prediction of final settlement using the Asaoka observation method, and finite element simulations using the Mohr-Coulomb and Hardening Soil models. Based on the analysis of the Asaoka method on monitoring data during the construction phase, the predicted final settlement (Sult) is 148.93 cm with a time to achieve a degree of consolidation of 90% (t90) of 1.27 years. The results of the Plaxis 2D simulation show an exponential relationship between the permeability value and the consolidation time. Through the back calculation analysis, the most representative soil permeability value (k) for the field conditions is 1.26 × 10?? m/day. This value validates the agreement between the numerical model and the actual consolidation behavior in the field, providing practical guidance for geotechnical engineers in soft soil design and construction monitoring.